Reactions of healthy persons and persons suffering from allergic rhinitis when exposed to office dust - Hauschildt, P; Mølhave, Lars; Kjærgaard, Søren K (Scandinavian Journal of Work, Environment & Health, 1999)
' ' OBJECTIVES ': 'Reactions to airborne office dust among healthy subjects and subjects suffering from allergic rhinitis were investigated.' ' METHODS ': 'Twelve healthy and 11 subjects suffering from allergic rhinitis were exposed to clean air [17 (SD 2) mg/m3] and office dust [439 (SD 68) mg/m3] for 245 minutes. The effect measurements included subjective sensations (questionnaire and potentiometer ratings), mood scale, peak flow, bronchial provocation with histamine using forced expiratory volume in 1 second as the effect measure, nasal mucosal swelling, tear film stability, epithelial damage, foam formation in the eye canthus, threshold for eye irritation with carbon dioxide, eye redness, cellular content of conjunctival fluid, and an addition test for distraction. As many investigations were made and as many statistical analyses (including subgroup analyses) were carried out, the risk of mass significance appeared. This problem was dealt with using the Bonferroni correction for multiple significance tests.' ' RESULTS ': 'The mean ratings of the potentiometer were higher (the subjects showed more irritation) during the dust exposure. The objective investigations showed only indications of effects of dust exposure, and some of the indications were in biologically unexplainable directions. No difference in the reactions to dust was observed between the healthy subjects and the subjects suffering from allergic rhinitis.' ' CONCLUSION ': 'Dust does not seem to have objective or subjective effects on humans, as only indications of dust effects were found. Subjects suffering from allergic rhinitis do not appear to be a risk group in relation to dust exposure.
Keywords: epithelial cell defect; eye redness; human exposure; tear-film stability; threshold for eye irritation with carbon dioxide